A Porous FeCuNi-Based Electrocatalyst Supported by Nickel Foam for Oxygen Evolution Reaction in Alkaline Conditions. Issue 14 (17th October 2018) - Dong, Yongzhi; Sun, Fengke; Li, Xi; Chu, Mei; Li, Na; Li, Xiaozheng; Wang, Lu; Qu, Deyu; Dong, Yulin; Xie, Zhizhong; Lin, Yawei; Zhang, Chaocan
Abstract : A porous FeCuNi-based catalyst on the Ni foam for the oxygen evolution reaction (OER) was fabricated in situ through a facile chronopotentiometry. XRD and XPS results verified that the prepared Fe2 Cu5 Ni mainly consisted of Fe2 O3, metallic Cu and Ni with a small amount of CuO and NiO. When the depositing time was 90 s, the current was 50 mA and the Fe/Cu molar ratio was 2:5, the catalyst Fe2 Cu5 Ni had the best catalytic activity with a smaller overpotential of 280 mV at 10 mA cm −2 and a lower Tafel slope of 50 mV dec −1 as well as an excellent stability. The improved performance could be due to the excellent eletrocatalytic activity from the three metal oxides, the good electronic conductivity from metallic Cu and Ni, the 3D porous structure of Ni foam and the flower-like nanosheets of Fe2 O3 or Cu. In conclusion, this work reveals that Fe2 Cu5 Ni could be an efficient catalyst for electrochemical water splitting devices blessed with its simple preparation, low cost, high catalytic performance and stability.